2018
DOI: 10.1590/s1980-220x2018010303412
|View full text |Cite
|
Sign up to set email alerts
|

Representations on adherence to the treatment of Multidrug-Resistant Tuberculosis

Abstract: Objective: To identify representations regarding adherence to the treatment of multidrug-resistant tuberculosis from the perspective of patients who were discharged upon being cured. Method: A qualitative study with patients who completed the drug treatment for multidrug-resistant tuberculosis in São Paulo. Social Determination was used to interpret the health-disease process, and the testimonies were analyzed according to dialectical hermeneutics and the discourse analysis technique. Results: Twenty-one pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 17 publications
0
9
1
10
Order By: Relevance
“…A tuberculose é reconhecidamente uma doença cuja ocorrência é influenciada por fatores sociais. Esse fato torna necessário que haja amparo governamental e a elaboração de políticas de apoio às pessoas doentes em vários aspectos, principalmente garantindo meios para a continuidade dos cuidados em saúde e promovendo ações de combate aos elementos originários do processo de adoecimento (FERREIRA KR, et al, 2018). O presente estudo identificou que as características sociodemográficas de raça, região de moradia, faixa etária e sexo, da população de um município do estado do Piauí no período estudado, estão diretamente ligadas à incidência da TB.…”
Section: Discussionunclassified
“…A tuberculose é reconhecidamente uma doença cuja ocorrência é influenciada por fatores sociais. Esse fato torna necessário que haja amparo governamental e a elaboração de políticas de apoio às pessoas doentes em vários aspectos, principalmente garantindo meios para a continuidade dos cuidados em saúde e promovendo ações de combate aos elementos originários do processo de adoecimento (FERREIRA KR, et al, 2018). O presente estudo identificou que as características sociodemográficas de raça, região de moradia, faixa etária e sexo, da população de um município do estado do Piauí no período estudado, estão diretamente ligadas à incidência da TB.…”
Section: Discussionunclassified
“…These individuals generally present physical weakness caused by the disease, resulting in decreased family income. 28 Based on the results of the research, a study conducted in Paraná, resembles that found in the research with 59% that make use of motorized transport, as for the expense in this same research, 45.2% was always spent what differs from what was found. 29 However, the results of the study conducted in Belém, differ completely from what was obtained.…”
Section: Discussionmentioning
confidence: 51%
“…Essa estratégia altera a rotina diária e gera constrangimentos no paciente quando realizado na unidade de saúde, um dos fatores associados à dificuldade de adesão ao tratamento (8) . Em São Paulo-SP, a necessidade dos pacientes em comparecer às consultas na unidade causava desgaste, devido ao longo trajeto, assim como condições inapropriadas do transporte público, comprometimento físico por causa da patologia e intervalo extenso de espera pela consulta (29) . É de responsabilidade municipal a operacionalização do TDO e o acompanhamento das medidas de prevenção.…”
Section: Resultsunclassified